OWNERSHIP CHANGES ON ARABLE LAND IN THE REPUBLIC OF SERBIA IN HISTORICAL PERSPECTIVE - Gnjatović, Dragana; Ljubojević, Ratko; Milutinović, Irina (Economics of Agriculture, 2012)
The subject matter of this paper is empirical investigation of the decisions of public policy making on the issue of arable land ownership during the two centuries of Serbian agricultural development. The goal of this investigation was to shed new light on the causes of long term economic backwardness of The Republic of Serbia. Following relevant historical facts that are incorporated in this work, we found constant and common factor to all historical phases of the development of land property rights. Our hypothesis was that frequent and insufficiently transparent changes of land property relations have always negatively affected economic activity because they left no time for strengthening the legal security of property owners. The result of our study is that the problem of ambiguity definition of land property rights in Serbian legislation has created room for inconsistencies in the implementation of agrarian reforms after the First and the Second World War. Special attention is paid to current changes in land ownership that take place within the process of denationalization and restitution of property seized after World War II, which are very slow and also inconsistent themselves.